2018
DOI: 10.3390/su10103457
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Capital Research: A Meta-Analysis and Implications for Management Sustainability

Abstract: The purpose of this study is to conduct a wide-ranging meta-analytic review of empirical psychological capital studies in the management field. We conducted a meta-analysis on papers collected from the EBSCOhost and ProQuest databases. For comprehensive and extensive literature coverage, we also searched and compared the Journal Citation Report for the journals that referenced the most-cited articles (e.g., Journal of Organizational Behavior, Academy of Management Journal, etc.). A total of 81 published types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 21 publications
9
42
0
Order By: Relevance
“…As mentioned earlier, the implementation of WFH for public organization potentially influence how employees perceive leadership, manage work-family interference, and perform their tasks via digital devices. This study confirmed the effect of Authentic Leadership on employees' PsyCap (Amunkete & Rothmann, 2015;Kong et al, 2018) and performance (Walumbwa et al, 2008(Walumbwa et al, , 2010Wang & Hsieh, 2013;Wang et al, 2014). Given that the employees work from home, this study also revealed that WFH did not hamper the positive impact of Authentic Leadership on employees' psychological states and performance.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As mentioned earlier, the implementation of WFH for public organization potentially influence how employees perceive leadership, manage work-family interference, and perform their tasks via digital devices. This study confirmed the effect of Authentic Leadership on employees' PsyCap (Amunkete & Rothmann, 2015;Kong et al, 2018) and performance (Walumbwa et al, 2008(Walumbwa et al, , 2010Wang & Hsieh, 2013;Wang et al, 2014). Given that the employees work from home, this study also revealed that WFH did not hamper the positive impact of Authentic Leadership on employees' psychological states and performance.…”
Section: Discussionsupporting
confidence: 77%
“…PsyCap has a negative association with some undesired employees' outcomes (Bitmiş & Ergeneli, 2015) and stress (Avey et al, 2009). A recent meta-analysis found that PsyCap was positively associated with Authentic Leadership (Kong et al, 2018). The evidence from Management and Psychology suggests that PsyCap fosters employees' positivity and attenuates many undesired employees' outcomes.…”
Section: The Effect Of Authentic Leadership On Performance Is Mediatementioning
confidence: 99%
“…PsyCap has been shown to be relevant for career, work attitudes, job satisfaction and performance, employee engagement, organizational citizenship behaviour, and perceptions of employability (Chiesa et al, 2018;Joo, Lim, & Kim, 2016;Kong et al, 2018;Paek et al, 2015;Soni & Rastogi, 2019;Wang et al, 2018). In their meta-analysis of PsyCap research, Kong et al (2018) confirmed that psychological capital is an intangible but powerful tool for affecting organizational behaviour, and that promoting the development of PsyCap should be a priority.…”
Section: Psychological Capital (Psycap)mentioning
confidence: 99%
“…The psychological capital is important in building a relationship between leaders and their followers (Kong et al, 2018), especially when taking on collective initiatives. It focuses on strengthening the virtues and merits of an organization (Luthans et al, 2004, 2007; Luthans and Youssef, 2004).…”
Section: Green Accountingmentioning
confidence: 99%